Exploring Various Flavors of Cilok Snacks for Profit: A Small and Medium Enterprises Activity by Students of Indo Global Mandiri University in Support of MBKM - Hidayahtullah, Hafiz; Hertati, Lesi; Asharie, Asmawati; Avini, Terti (CV. Proaksara Global Transeduka, 2023)
The MSME activity carried out by Indo Global Mandiri University students, entitled